1997
DOI: 10.1046/j.1365-2141.1997.d01-2123.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 8 in a patient who responded to therapy with all‐trans‐retinoic acid and developed paroxysmal nocturnal haemoglobinuria

Abstract: Trisomy 8 is the most common numerical chromosomal abnormality in myelodysplastic syndromes (MDS). Paroxysmal nocturnal haemoglobinuria (PNH) is an aquired haemolytic anaemia, clonal in nature, due to somatic mutation. PNH may evolve to aplastic anaemia, to MDS or to acute myeloid leukaemia. We present a patient who had trisomy 8 mosaicism at disease presentation who received therapy with all‐trans‐retinoic acid, responded to therapy, and developed PNH in the course of the disease. Cytogenetics at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Apart from the patients suffering from de novo PNH, pathological links to other stem cell disorders like AA and MDS have often been described (Jin et al., 1996; Nishimura et al., 1996; Teramura & Mizoguchi, 1996; Viniou et al., 1997; Iwanaga et al., 1998; Azenishi et al., 1999; Schrezenmeier et al., 2000; Socie et al., 2000). For example, in a study investigating 40 patients with MDS, 10% of the patients showed an increased percentage of GPI‐deficient cells (Iwanaga et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the patients suffering from de novo PNH, pathological links to other stem cell disorders like AA and MDS have often been described (Jin et al., 1996; Nishimura et al., 1996; Teramura & Mizoguchi, 1996; Viniou et al., 1997; Iwanaga et al., 1998; Azenishi et al., 1999; Schrezenmeier et al., 2000; Socie et al., 2000). For example, in a study investigating 40 patients with MDS, 10% of the patients showed an increased percentage of GPI‐deficient cells (Iwanaga et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente se están haciendo estudios con la eritropoyetina recombinante humana (16) (pues, se supone que sólo estimula los clones normales de hematíes) y el ácido transretinoico (de forma muy limitada, ya que sólo se ha obtenido aumento del nivel de hemoglobina en patología asociada a trisomía 8) (17).…”
Section: Monocitosunclassified